Integrating nucleic acid sequence-based amplification and microlensing for high-sensitivity self-reporting detection. Issue 23 (23rd September 2020) - Teng, Feiyue; Wu, Xinpei; Hong, Tao; Munk, Gary B.; Libera, Matthew
Abstract : We use electron-beam patterned functional microgels to integrate self-reporting molecular beacons, dielectric microlenses, and solid-phase and/or solution-phase nucleic acid amplification in a viral-detection microarray model. Abstract : We use electron-beam patterned functional microgels to integrate self-reporting molecular beacons, dielectric microlenses, and solid-phase and/or solution-phase nucleic acid amplification in a viral-detection microarray model. The detection limits for different combinations of these elements range from 10 −10 M for direct target-beacon hybridization alone to 10 −18 M when all elements are integrated simultaneously.